STRUKTUR KOMUNITAS, ZONASI DAN KEANEKARAGAMAN HAYATI VEGETASI MANGROVE DI SEGARA ANAKAN CILACAP - Endang Hilmi; Asrul Sahri Siregar; Luvianna Febryanni (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2015)
Mangrove ecosystem of Segara Anakan Cilacap has specific vegetation, function, and benefit. It was dominated by Rhizophora, Bruguiera, Avicennia and associate vegetation such as Nypa frutican. Stability of mangrove ecosystem can be seen by community structure, zonation and diversity of mangrove vegetation. This research aimed to analyze community structure, zonnation and diversity of mangrove vegetation in Segara Anakan Lagoon. This research used survey method with cluster sampling by stratified analysis. The Analyze of data used association analysis, zonation analysis, richnes index, and Shanon Wiener index. This Research showed that (1) Association index of seedling was dominated by index < 0.22 (lowest association) with scored 46,67 % - 66.66 %, (2) Association index of sapling also was dominated by index < 0.22 (lowest association) with scored 58,33% - 71.43 %, (3) Association index of tress also was dominated by index < 0.22 (lowest association) with scored 67,27 % % (4) Overlaping indeks showed Aegiceras corniculatum has high overlap toward Nypa frutican (71 %) (seedling stage) and Rhizophora apiculata to Avicennia spp (0,49) (sapling stage). (5) Zonation of mangrove showed that Zone 1 as direct connecting zone with sea which were dominated by Avicennia marina and Avicennia oficinallis. Zone 2 as the middle zone which were dominated by Rhizophora mucronata, Rhizophora apiculata, and Ceriops tagal. Zone 3 as direct connecting zone with island which were dominated by Nypa fruticans, Acanthus ilicifolius, and Sonneratia casseolaris (6) diversity index between 0.48 – 1.83 (low – middle).Keywords : mangrove vegetation, acosiation index, zonation, community structure and diversity